Sex differences in acute respiratory tract infections—multi-year analysis based on data from a large tertiary care medical center in Israel - Peer, Victoria; Mandelboim, Michal; Jurkowicz, Menucha; Green, Manfred S. (Frontiers in Public Health, 2025)
IntroductionAcute respiratory tract infections impose a considerable burden on the health services. The development of improved prevention and treatment measures requires a better understanding of the mechanisms of infection. Since sex has been shown to be an important biological variable in the immune response to infections, we aimed to assess sex differences in the incidence rates of respiratory infections.Materials and methodsWe obtained data on cases hospitalized with diagnosed respiratory tract infections by sex and age group over a period of 11 years (2012–2022) from the Sheba Medical Center (SMC), the largest tertiary care medical center in Israel. Nasopharyngeal samples collected from the patients with symptoms of a respiratory tract infection were examined for adenovirus, influenza, rhinovirus, parainfluenza-3, human metapneumovirus (hMPV) and respiratory syncitial virus (RSV) in the Central Virology Laboratory and Viral RNA/DNA was extracted and tested using a real-time reverse transcription-PCR (rRT-PCR) assay. We calculated annual male to female incidence rate ratios (IRRs) which were combined over the period of the study using meta-analysis methodology.ResultsThere was a male excess in infection rates for all viruses, particularly in the youngest age groups of <0 and 1–4 years. Our analyses revealed that the influenza incidence rates were 42 and 28% higher in males in infants and toddlers. The male dominance was similar for adenovirus with 33 and 38% in infancy and age group 1–4. For RSV, the male to female IRR was higher at ages <1 and 1–4 (22 and 21% respectively). Males were more likely to be positive for rhinovirus in infancy and toddlers, by 40 and 25%, respectively.ConclusionThere is evidence of an excess incidence of respiratory diseases in males. The mechanism is unclear. Other than behavioral factors, there is a need to study the role of sex hormones and genetic factors.